Gerakan Literasi Sekolah Dalam Menumbuhkan Minat Baca Siswa di SDN Benua Anyar 8 Banjarmasin - Naila Lutfiana; Ahmad Suriansyah; Arta Mulya Budi Harsono; Aldy Ferdiyansyah; Rianty Yulandra (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
This study aims to identify the role of the School Literacy Movement in enhancing students' reading interest at SDN Benua Anyar 8. The research employs a qualitative method with a case study approach, involving the principal, teachers, and participants from the Kampus Mengajar program. The findings reveal that the principal serves as the main driving force, supported by teachers, students, and collaboration with parents and Kampus Mengajar participants. GLS activities, such as weekly literacy programs and interactive learning media, have successfully increased students' motivation to read. The challenges identified include a lack of reading materials, inadequate library conditions, and students' initial low interest in reading. Through innovative strategies and collaboration among various stakeholders, the School Literacy Movement has successfully fostered a literacy culture within the school.